The Anatomy of Human Motivation: Arrays of What they Say, Think, Behave and Act with Reference to Blood Type - Shyam B. R; P. S. Aithal (International Journal of Management, Technology and Social Sciences (IJMTS), 2022)
Purpose: This research sheds light on motivation. Motivation is the key to performance improvement. Despite enormous research, basic as well as applied, the subject of motivation is not clearly understood and more often it is poorly practiced. To understand motivation, one must understand human nature itself and there lies the problem. Blood is the most fundamental nourishment for our bodies. It seems to be that different blood types would react differently & motivate differently. Many other factors also influence our personality same way as motivation. Maybe blood type should be used for more than just matching organ donors, same way may be blood type could also be good for watching which blood type stimulates which motivation type/behaviour & to find which is the best blood type motivation. Objective: The researchers have set the following primary objective and the current study investigates 2 broad research questions: This research aims to examine which blood type stimulates which motivation type/behaviour & to find which is the best blood type motivation. Design/Methodology/Approach: The study is based on both secondary & primary evidence. Hypotheses are stated for the various variables selected and analyzed to prove or disprove the same without any errors. The designed questionnaire includes demographic factors and human resource motivation with reference to blood type-related close-ended structured questionnaire in the form of 5 points Likert scale. The primary data are collected from 128 various professionals of different domiciles by using a convenient random sampling technique. The analysis of the research work is carried out with the help of SPSS software (21.0), wherein, descriptive statistics are used to describe the nature of the data. Factor analysis is used to check the commonalities and homogeneous grouping of the factors amongst the variables. Reliability tests are used to understand how reliable the data grouping. A statistical tool like one-way ANOVA is used to find the relationships between the factors. Findings/Result: Previously nobody studied the anatomy of human resource motivation with reference to blood type. The present study made an attempt which blood type stimulates which motivation type/behaviour & to find which is the best blood type motivation. The study is based on primary evidence. With these two epilogues proven we can say that there is a stimulation of different blood types on motivation type/behaviour & the best blood type motivation. The challenge of blood type stimulates motivation type/behaviour is not peculiar to any place or profession; hence the problem is more accentuated. Many industrialists have understood the importance of overwhelming the challenges of Human Resources and other problems related to them, hence the motivation type/behaviour need to be tackled with the weapon of trend and addressing motivational techniques and it is beyond monetary terms for which the blood type stimulates motivation type/behaviour. Research Limitations/Implications: In the present research an attempt is made by the researchers to understand the research gap in the area hence a conceptual model is proposed towards the end of the study and the research goes further to advance significance to discover motivation type/behaviour of individuals & to find which is the best blood type motivation. The researchers also give an insight into the objectives framed. Originality/New Knowledge/Interpretation/Value: Many of the earlier studies have proved that the blood type of individuals does have statistical significance on their personality and behaviours. Similarly, blood type stimulates motivation type/behaviour. Countries like Japan, Korea, Asia etc., have proved that blood type does have an effect on motivation process, theories & behaviours as these countries do believe in the theories of personality and other motivational aspects. Hence, this study helps in concluding that, individuals tend to change their personality and motivation factors to be connected with the blood type rather than in self-fulfilling prophecy in many of the motivational factors. Addressing further, the comprehensive picture is analyzed with the various blood type that associates with the considerable motivation factors and various functions associated to come up with the behavioural aspect of individuals. This study has helped to understand the desire to get good extrinsic, or is it a competitive drive intrinsic? Motivation can be intrinsic or extrinsic (or perhaps both). Paper Type: Present study made an attempt to examine which blood type stimulates which motivation type/behaviour & to find which is the best blood type motivation. The study is based on primary evidence.